Physiologic Responses to Feeding Rumen-Protected Glucose to Lactating Dairy Cows - J. A. Sauls-Hiesterman; S. Banuelos; B. Atanasov; B. Bradford; J. S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2018)
Lactating Holstein cows were enrolled in a study beginning before first insemination. Cows were supplemented with a rumen-protected glucose (RPG) product to test the hypothesis that circulating progesterone concentrations could be increased by increasing blood glucose, which causes an increase in insulin, subsequently decreasing progesterone clearance by liver enzymes. Supplementation occurred at 0, 2.2, 4.4, or 8.8 lb per head per day to test a dose response. Treatment began 3 days before ovulation and continued until day 12 of the estrous cycle. Rumen-protected glucose did not impact serum concentration of glucose before or after feeding, but the change in insulin concentration (post-feeding – pre-feeding) was greater for the control cows compared with cows that received the three doses of RPG. Crude protein (CP) intake and milk urea nitrogen (MUN) increased linearly with treatment, but dry matter intake (DMI) and milk yield were unaffected by treatment. Concentrations of progesterone were unaffected by treatment, and pregnancy risk at first insemination was reduced by treatment. Rumen-protected glucose failed to increase serum insulin or progesterone concentrations.
Keywords: glucose; insulin; progesterone